ANALISIS KINERJA USAHA MIKRO KECIL DAN MENENGAH DI KOTA MAKASSAR - Syamsul Alam (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
Access information is positive and significant effect on the Performance of Micro, Small and Medium Enterprises. It can be seen from the value t count > t table (3.240 > 2.020) and a significant value < significance level (α) 0.05 ( 0.002 < 0.05). Marketing communications positive and significant effect on the Performance of Micro, Small and Medium Enterprises. It can be seen from the value t count > t table (5.632 > 2.020) and a significant value < significance level (α) 0.05 ( 0.000 < 0.05) . Access to Information and marketing communications simultaneously positive and significant impact on the performance of Micro, Small and Medium Enterprises. It can be seen from the value of F count> F table ( 34.254 > 3.226 ) and a significant value < significance level (α) 0.05 (0.000 < 0.05) .